Yi–Qi–Jian–Pi–Xiao–Yu–Xie–Zhuo Formula Improves Muscle Atrophy via Modulating the IGF-1/PI3K/Akt Signaling Pathway in 5/6 Nephrectomized Rats - Xia, Hong; Zhang, Bingbing; Yang, Dan; Zhu, Chengyue; Zhang, Jiudan; Chen, Hongbo; Ma, Hongzhen; Hu, Shouci; Xu, Chao; Shi, Chengqian; Lu, Keda; Zhang, Peipei (Frontiers in Pharmacology, 2021)
Yi-Qi-Jian-Pi-Xiao-Yu-Xie-Zhuo (YQJPXYXZ) formula is used for treating chronic kidney disease (CKD) for many years with good efficiency based on cumulative empirical experience of previous practitioners. Impairment of IGF-1/PI3K/Akt signaling pathway plays an important role in mediating muscle wasting. This study aimed to observe effects of YQJPXYXZ formula on muscle atrophy in CKD rats and investigate its possible mechanism on regulation of the IGF-1/PI3K/Akt signaling pathway. The 5/6 nephrectomised rats were randomly allocated into 3 groups: CKD group, KT (Compound α-Ketoacid Tablets) group and YQJPXYXZ group. Besides, a sham-operated rats as Sham group. All rats were treated for 12 weeks. Results showed that administration of YQJPXYXZ formula prevented body weight loss, muscle fiber size decrease. Moreover, YQJPXYXZ formula increased the IGF-1 level of serum and skeletal muscle in CKD rats, and enhanced phosphorylation level of Akt. 52 Furthermore, YQJPXYXZ formula decreased the Atrogin1 and MuRF1 mRNA and 53 MuRF1 protein. In conclusion, our data demonstrated that YQJPXYXZ formula 54 improves muscle wasting in CKD rats, which might be associated with the modulation 55 of IGF-1/PI3K/Akt signaling pathway and inhibition of ubiquitin-proteasome system 56 (UPS).